Community voices on climate, peace and security: Senegal - Medina, Leonardo; Krendelsberger, Alexandra; Renkamp, Theresa; Madurga Lopez, Ignacio M.; Pacillo, Grazia; Läderach, Peter R.D.; Hellin, Jon; Sieber, Stefan; Bonatti, Michelle (CGIAR FOCUS Climate Security, 2023)
This study conducted a participatory appraisal of climate vulnerabilities and conflict risks five communities across Senegal: 1) pastoral, agro-pastoral and farming communities in the drylands areas of Louga 2) farmer and agro-pastoral communities in Kaffrine, 3) fishing communities on the islands of the coastal area of Casamance, 4) relocated fishing communities in Saint Louis, and 5) displaced farming communities in the tropical forests of Casamance. 1) pastoral, agro-pastoral and farming communities in the drylands areas of Louga 2) farmer and agro-pastoral communities in Kaffrine, 3) fishing communities on the islands of the coastal area of Casamance, 4) relocated fishing communities in Saint Louis, and 5) displaced farming communities in the tropical forests of Casamance. Senegal's vulnerability to climate change is evident in the rising temperatures, shifting precipitation patterns, and sea-level rise that impact the country. The consequences of these climatic changes are intensifying the existing vulnerabilities of local communities and exacerbating issues related to societal stability and conflict. Climate change-induced resource scarcity, such as limited access to water and arable land, can lead to disputes within and between communities. The threats posed by climate change to agricultural livelihoods are also undermining the ability of local communities to collaborate in addressing climate-related challenges, eroding social cohesion. In addition, climate-induced displacement and migration are becoming more common as people search for more habitable areas. Nevertheless, Senegal, as a whole, remains relatively stable and peaceful compared to other regions in the Sahel. Conflict-sensitive resilience building action needs to be deployed in accordance with community-level priorities, in a way that builds upon local and Indigenous knowledge, everyday experience of problem dynamics, and perceptions around structural sources of vulnerability and conflict. Community members developed context-specific policy recommendations to turn climate-related security risks into opportunities for resilience and peacebuilding.